Evidence for a Jeff=0 ground state and defect-induced spin glass behavior in the pyrochlore osmate Y2Os2O7 - Davies, N; Topping, C; Jacobsen, H; Princep, A; Kirschner, F; Rahn, M; Bristow, M; Vale, J; Da Silva, I; Baker, P; Sahle, C; Guo, Y; et al. (American Physical Society, 2019)
We present AC and DC magnetometry, heat capacity, muon spin relaxation (μSR), and resonant inelastic x-ray scattering (RIXS) studies of the pyrochlore osmate Y2Os2O7. Consistent with previous results, we observe a small Curie-Weiss effective moment of approximately 0.4 μB and spin freezing at a temperature Tf≃5K. On the other hand, our analysis of the RIXS spectra with single-ion energy-level calculations implies a nonmagnetic Jeff=0 ground state on the Os4+ sites, with the spin-orbit interaction, Hund's coupling, and trigonal distortion of OsO6 octahedra, all important in modeling the observed spectra. From high-field magnetization data, we show that the paramagnetic moment is most likely due to large moments μeff≃3μB on only a small fraction f≃0.02 of Os sites. We suggest disorder-related effects, such as oxygen nonstoichiometry or site interchange between Os and Y ions, as the most likely explanation for the magnetic response of this material.